Reconciling internal and external performance in a holistic approach: A Bayesian network model in higher education. Issue 5 (1st April 2015) - Di Pietro, Laura; Guglielmetti Mugion, Roberta; Musella, Flaminia; Renzi, Maria Francesca; Vicard, Paola
Highlights The paper innovatively proposes the use of BNs in higher education sector. A holistic approach is adopted to jointly monitor internal and external indicators. Most relevant variables affecting KPI were identified by mutual information analysis. Results point out the critical issues of the analyzed Master degree.